A coil system for real-time magnetic fluid hyperthermia microscopy studies. (17th February 2016) - Subramanian, Mahendran; Miaskowski, Arkadiusz; Pearce, Gillian; Dobson, Jon
Abstract: Purpose : We describe the design and application of a new apparatus for applying Radiofrequency (RF) electromagnetic fields to cells in culture on a microscope stage. This new design enables real-time studies of the actuation of magnetic nanoparticles bound to membrane receptors or internalised within cells together with the study of magnetic fluid hyperthermia (MFH)-associated effects. Materials and methods : RF coils were fabricated and electromagnetic simulations were performed along with compatibility evaluations and calorimetric experiments using this apparatus at discreet frequencies between 100 kHz and 1 MHz. Cell killing via MFH was investigated in a neuroblastoma tumour cell line. Results : Simulations and evaluations showed that the field intensity and homogeneity experienced by the cells within the chamber is best with a planar coil configuration. The incubation chamber was suitable for cell culture and the design was compatible with mountings on different makes of microscopes as it mimics a standard 96/24/6 tissue-culture well plate. Successful calorimetric and MFH cytotoxicity proof-of-principle experiments were performed and are presented. Conclusions : We conclude from these experiments that alternating magnetic field (AMF)-mediated activation and magnetic fluid hyperthermia (MFH) research will benefit from this RF coil that fits inside an incubation chamber, mounted onto a microscope. This new design could be used to assist real-time MFH studies in vitro .